2020
DOI: 10.1021/acsami.0c12561
|View full text |Cite
|
Sign up to set email alerts
|

Processing Natural Wood into a High-Performance Flexible Pressure Sensor

Abstract: Flexible pressure sensors have received wide attention because of their potential applications in wearable electronics and electronic skins (e-skins). However, the high performance of the pressure sensors relies principally on the introduction of complex surface microstructures, which often involves either complicated procedures or costly microfabrication methods. Moreover, these devices predominantly use synthetic polymers as flexible substrates, which are generally nonbiodegradable or not ecofriendly. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 43 publications
(74 reference statements)
0
45
0
Order By: Relevance
“…Examples include identifying complex arterial pulse signals, thus highlighting its potential applications in real-time healthcare and medical diagnostics. [145] Reprinted with permission from Ref. 144 Adapted with permissions from Carbohydrate Polymers.…”
Section: Cellulose Gel For Flexible Sensing Applications In Medical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include identifying complex arterial pulse signals, thus highlighting its potential applications in real-time healthcare and medical diagnostics. [145] Reprinted with permission from Ref. 144 Adapted with permissions from Carbohydrate Polymers.…”
Section: Cellulose Gel For Flexible Sensing Applications In Medical Treatmentmentioning
confidence: 99%
“…Fig.11(a)Various flexible, skin-mountable, and wearable strain sensors made of functional nanomaterials-polymer composites. Reprinted with permission from Ref 145. Adapted with permissions from ACS Applied Materials & Interfaces.…”
mentioning
confidence: 99%
“…Guan et al turned natural saw-cut wood into a flexible pressure sensor by chemical treatment and rGO coating. 180 This flexible wood-based wearable device can precisely detect finger movement, acoustic vibration, and arterial pulse signal. It has a fast response time of 150 ms, high sensitivity of 1.85 k Pa À1 over a wide linear range of 0-60 k Pa À1 , and very long stability of 1000 cycles.…”
Section: Sensors and Nanogeneratorsmentioning
confidence: 99%
“…Balsa wood was chosen as the starting material because of its low density, a unique 3D porous structure with multiple channels and a thin cell wall (Figure S1, S2, Supporting Information), which make it easier to partially destroy the cell walls. [27,28] The wood cell wall was a robust assembly of stiff cellulose fibrils intertwined with the matrix polymers of hemicelluloses and lignin, [29] hence it was rigid and was easily broken upon bending (Figure S3; Video S1, Supporting Information). The NW was made flexible by partially removing the lignin and the hemicellulose from the cell walls via the NaOH/Na 2 SO 3 chemical treatment.…”
Section: Synthesis Nanostructures and Characterization Of Fw/mwcnt/ag/pedot:pssmentioning
confidence: 99%
“…The hemicellulose and the partial cellulose can be dissolved in an alkaline solution containing sulfite. [28] The Fourier Transform infrared spectroscopy (FTIR) (Figure 2b) showed that the peaks at 1736 and 1235 cm −1 for the carbonyl and C-O stretching were significantly reduced, reflecting a remarkable hemicellulose removal. Meanwhile, the decline of the peaks at 1593 and 1505 cm −1 yielded an aromatic skeleton, showing lignin partial removal during the NaOH/Na 2 SO 3 treatment.…”
Section: Synthesis Nanostructures and Characterization Of Fw/mwcnt/ag/pedot:pssmentioning
confidence: 99%